11 books expanding Tan Lin's Seven controlled vocabularies and obituary 2004 - Lin, Tan 1957-; Alexander, Chris; Snelson, Daniel; Aubert, Danielle 1975-; Brown, Lee Ann (Edit Publications, 2010)
This volume contains essays (max. 600 words) by forty-seven contributors on technology, tools and concepts related to writing, translating, publishing and editing, such as select bibliographies, font libraries, Facebook, Blurb, metadata, scanning, artist’s books, poetry workshops, PowerPoint, IBM Selectric II, Xerox, Microsoft Word, errata, pagination, barcodes, and indexes. ...
Keywords: Künstlerbuch